How stabilizing selection and nongenetic inheritance combine to shape the evolution of phenotypic plasticity. (29th April 2019) - Levis, Nicholas A.; Pfennig, David W.
Abstract: Relatively little is known about whether and how nongenetic inheritance interacts with selection to impact the evolution of phenotypic plasticity. Here, we empirically evaluated how stabilizing selection and a common form of nongenetic inheritance—maternal environmental effects—jointly influence the evolution of phenotypic plasticity in natural populations of spadefoot toads. We compared populations that previous fieldwork has shown to have evolved conspicuous plasticity in resource‐use phenotypes ("resource polyphenism") with those that, owing to stabilizing selection favouring a narrower range of such phenotypes, appear to have lost this plasticity. We show that: (a) this apparent loss of plasticity in nature reflects a condition‐dependent maternal effect and not a genetic loss of plasticity, that is "genetic assimilation, " and (b) this plasticity is not costly. By shielding noncostly plasticity from selection, nongenetic inheritance generally, and maternal effects specifically, can preclude genetic assimilation from occurring and consequently impede adaptive (genetic) evolution.